Myotubularin-Related Phosphatase 3 Promotes Growth of Colorectal Cancer Cells - Bo’an Zheng; Xiaojun Yu; Rui Chai (The Scientific World Journal)
Due to changes in lifestyle, particularly changes in dietary habits, colorectal cancer (CRC) increased in recent years despite advances in treatment. Nearly one million new cases diagnosed worldwide and half a million deaths make CRC a leading cause of cancer mortality. In the present study, we aimed to investigate the role of myotubularin-related phosphatase 3 (MTMR3) in CRC cell growth via lentivirus-mediated small interfering RNA (siRNA) transduction in human colon cancer cell lines HCT116 and SW1116. The effect of MTMR3 knockdown on cell growth was evaluated by MTT, colony formation, and flow cytometry assays. The effect of MTMR3 knockdown on cell apoptosis was evaluated by flow cytometry with Annexin V/7-AAD double staining. The activation of apoptotic markers, Bad and PARP, was detected using Intracellular Signaling Array. Knockdown of MTMR3 resulted in a significant reduction in cell proliferation in both HCT116 and SW1116 cells. Moreover, knockdown of MTMR3 led to S phase cell cycle arrest. Furthermore, knockdown of MTMR3 induced cell apoptosis via phosphorylation of Bad and cleavage of PARP. These results indicate that MTMR3 may play an important role in the progression of CRC and suggest that siRNA mediated silencing of MTMR3 could be an effective tool in CRC treatment.